Developing Emotional Skills and the Therapeutic Alliance in Clients with Alexithymia: Intervention Guidelines - Silva, Ana Nunes Da (2021)
Despite being a longstanding and well-established concept, alexithymia is unfamiliar for many clinicians. This article aimed to address the alexithymia concept from a clinical perspective based on a review of the research on alexithymia intervention. Several strategies are proposed to help clinicians better work with alexithymic clients in psychotherapy. Alexithymia assessment, its impact on the therapeutic alliance, and the difficulties in emotional tasks are highlighted points. Considering alexithymia will inform clinicians’ current diagnosis and conceptualization and provide specific targets and venues for intervention, increasing the effectiveness of psychotherapy.